My nest of silence - Faulkner, Matt (Atheneum Books for Young Readers, 2022)
A graphic novel/prose hybrid which tells the story of a young Japanese American man who leaves his family in the Manzanar internment camp to fight in the European theater during World War II, and of his ten-year-old sister who, frustrated over her brother risking his life for the government that imprisoned them, decides to stop talking until he returns.